Determination of children and teenagers economical socialization: theoretic analysis - A l Zhuravlev; T V Drobysheva (Peoples' Friendship University of Russia (RUDN University), 2009)
The different types of determinants in general and socio-psychological factors, in particular, children and teenagers economical socialization are studying in this work; the structure and matter of two major determinants: school economical education and home economical education are analyzing here.